Appropriateness of pediatric outpatient transthoracic echocardiogram orders following cessation of an active educational intervention. (8th October 2018) - Anderson, Shae; McCracken, Courtney E.; Sachdeva, Ritu
Abstract: Objective: The educational intervention (EI) through the Pediatric Appropriate Use of Echocardiography (PAUSE) multicenter study resulted in improved appropriateness of transthoracic echocardiogram (TTE) orders at our center. The current study evaluated if this pattern persisted after cessation of EI and the potential physician characteristics influencing appropriateness. Design: Outpatients (≤18 years old) seen for initial evaluation during the EI (July to October, 2015) and 6‐month post‐EI (May to August, 2016) phases were included. Comparison was made between TTE rates and appropriateness ratings during EI and post‐EI phase. Association between TTE rate and appropriateness with physician characteristics (age, experience, patient volume, and area of practice) was determined using odds ratio. Results: The study included 7781 patients (EI: N  = 4016; post‐EI: N  = 3765) seen by 31 physicians. Comparison of appropriateness ratings in a randomized sample (EI: N  = 1270; post‐EI: N  = 1325 patients) showed no significant differences between the two phases (appropriate: 75.2% vs 74.9%, P = .960; rarely appropriate 4.1% vs 6.5%, P = .065). Though there was significant variability among physicians for TTE order appropriateness ( P = .044) and ordering rate ( P <.001), none of their characteristics were associated with appropriateness and only a higher patient volume was associated with decreased odds of TTE ordering (OR =0.7). Conclusion: The PAUSE study EI resulted in maintaining appropriate utilization of TTEs at our center for 6 months following its cessation. Though not statistically significant, there was a trend toward increase in the proportion of studies for indications designated rarely appropriate (R). There was significant physician variability in TTE ordering and appropriateness during both phases. Development of EI to reduce physician variability and integration of EI with provider workflow may help sustain appropriate TTE utilization.